Exploring the efficacy of nortriptyline, buspirone, and Ginkgo biloba extract as alternative medications in ADHD management: a systematic review - Ramin Abdi Dezfouli; Soroush Hashemzadeh; Anita Saleh Mohammadzadeh (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Attention-Deficit/Hyperactivity Disorder (ADHD) is commonly managed with stimulant medications such as methylphenidate and non-stimulant options like atomoxetine. However, not all patients respond well or tolerate these standard treatments, highlighting the need for alternative therapeutic strategies. While some off-label medications have shown promise in managing ADHD symptoms, there are other agents that have received little attention. Given this context, this systematic review compiles the existing data and evaluates the use of nortriptyline, buspirone, and Ginkgo biloba extract as non-traditional off-label alternatives in managing ADHD symptoms. Results Of the initial 821 studies, 12 studies were included. Buspirone showed improvements (moderate certainty) primarily in children, with mild and temporary side effects (moderate certainty). Ginkgo biloba also showed improvements (low certainty), especially in children, with minimal side effects (moderate certainty). Finally, nortriptyline caused improvements in ADHD symptoms (low certainty), particularly in those with comorbid conditions. Dry mouth and dizziness were reported as side effects of nortriptyline. Reasons for low–to–moderate certainties were the small number of studies, small sample sizes, and reliance on open-label designs. Conclusions These non-standard treatments might serve as adjunctive or alternative options, particularly in patients who are intolerant to first-line medications. However, they cannot currently be recommended as primary treatment options due to the lack of robust evidence. Further well-designed randomized controlled trials are needed to establish their efficacy, optimal dosing, long-term safety, and comparative effectiveness against established treatments. Although the side effects of Ginkgo biloba and buspirone were well tolerated in the used doses, the cardiovascular side effects of nortriptyline (especially in children) should be taken into account. Graphical Abstract